Islamic Studies in Higher Education in Indonesia: Challenges, Impact and Prospects for the World Community - Abdullah, Muhammad Amin (Al-Jami'ah Research Centre, 2017)
In the global socio-political situation today, where rigid, extreme and radical interpretations of religion are commonly found and widespread, the contribution of Indonesian post-graduate education, especially Islamic higher education, come to the front stage and become a topic of serious discussion. In term of education in Indonesia, there is an unavoidable fact that Islamic education including Islamic higher education is not a new phenomenon. The situation led to the fact that some international Islamic scholars began to consider the Islamic higher education in Indonesia as a potential alternative system of graduate education including religious education and its contents and methods in offering innovation and transformation. This seems to be much more conducive approach and research to local, regional and global community and peace. This article will explain descriptively the long history of Islamic education and its development. It also aims at presenting elaboration on how higher education of indigenous Islam can modify their own teaching and research methodologies to be more relevant to the intellectual development and advancement, especially that of sciences and humanities in particular. The focus will be on: what are the key issues and elements of the Indonesian Islamic higher education leading to significantly change and contribute to the welfare of the nation and mankind, especially on the development of research which seems to illustrate the weakness of previous educational institutions system in Indonesia. Moreover, there is one thing to remember that the worldwide academic community cannot wait for any longer the solution strongly expected to reduce the weakness since development of religious education and Islam in the Middle East, South Asia, and some parts of the Muslim world is not, more or less, promising for the sake of global humanity, prosperity and peace.[Pada situasi sosial-politik global dewasa ini, ketika interpretasi agama yang rigid, ekstrim dan radikal meluas dan mudah dijumpai, kontribusi pendidikan tinggi, khususnya perguruan tinggi Islam, harus tampil dan menjadi bahan diskusi serius. Dalam konteks pendidikan di Indonesia, terdapat fakta tak terbantahkan bahwa pendidikan Islam termasuk pendidikan tinggi Islam, bukanlah hal baru. Situasi di Indonesia ini mendorong akademisi Islam internasional untuk mempertimbangkan pendidikan tinggi Islam sebagai alternatif dalam inovasi dan transformasi pendidikan, baik dalam hal materi ataupun metodologi. Tulisan ini menjelaskan sejarah panjang perkembangan pendidikan Islam. Selain itu, juga mengelaborasi bagaimana sistem pendidikan Islam memodifikasi metode pengajaran dan risetnya agar lebih sesuai dengan perkembangan dan capaian ilmu pengetahuan, khususnya ilmu sosial humaniora dewasa ini. Tulisan ini berfokus pada isu-isu dan unsur-unsur kunci pendidikan tinggi Islam yang sekiranya mampu berkontribusi dalam mewujudkan kesejahteraan umat manusia dan bangsa, khususnya perkembangan riset yang memetakan kelemahan dari sistem pendidikan di Indonesia. Oleh karena itu, satu hal yang harus diingat bahwa komunitas akademik dunia tidak bisa menunggu lebih lama lagi solusi untuk menutupi kekurangan - kekurangan tersebut, terlebih karena perkembangan pendidikan agama dan Islam di Timur Tengah, Asia Selatan, dan wilayah lain dunia Islam tidak terlalu menjanjikan terhadap kemanusiaan, kesejahteraan, dan perdamaian global.]